2012
DOI: 10.1007/s10311-012-0357-3
|View full text |Cite
|
Sign up to set email alerts
|

High immobilization of soil cesium using ball milling with nano-metallic Ca/CaO/NaH2PO4: implications for the remediation of radioactive soils

Abstract: This report shows that cesium can be immobilized in soils with an efficiency of 96.4% by ball milling with nano-metallic Ca/PO 4 . In Japan, the major concern on 137 Cs deposition and soil contamination due to the emission from the Fukushima Daiichi nuclear power plant showed up after a massive quake on March 11, 2011. The accident rated 7, the highest possible on the international nuclear event scale, released 160 petabecquerels (PBq) of iodine 131 I and 15 PBq of 137 Cs according to the Japanese Nuclear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This mixture was found to be more suitable for trapping heavy metals in soil with an efficiency of more than 99% (Mallampati et al, 2012a). The same Ca/CaO mixtures proved to be effective in retaining 133 Cs after a ball-milling process (Mallampati et al, 2012b). Further, the nanometallic Fe/Ca/CaO system was found to be equally efficient in fixing and encapsulating heavy metals in a pozzolanic cemented shell (Mallampati et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…This mixture was found to be more suitable for trapping heavy metals in soil with an efficiency of more than 99% (Mallampati et al, 2012a). The same Ca/CaO mixtures proved to be effective in retaining 133 Cs after a ball-milling process (Mallampati et al, 2012b). Further, the nanometallic Fe/Ca/CaO system was found to be equally efficient in fixing and encapsulating heavy metals in a pozzolanic cemented shell (Mallampati et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, the particle surface area increases and the heavy metal mobility decreases because the adsorption area increases (Orumwense, 2006). However, during grinding with nano-Fe/Ca/CaO/PO 4 additives, fly ash particles are subjected to collisions that are expected to promote aggregation and breakage phenomena (Montinaro et al, 2007 (Figure 4b) (Mallampati et al, 2012a(Mallampati et al, , 2014. The X-ray diffraction (XRD) patterns of fly ash before treatment consisted mainly of a glassy phase and some minerals with crystalline phases of mullite and quartz (SiO 2 ), magnetite (Fe 3 O 4 ), anorthite (CaAl 2 Si 2 O 8 ), and hematite (Fe 2 O 3 ).…”
Section: Heavy Metal Immobilization and Separationmentioning
confidence: 99%
“…Our recent investigations revealed that a nanometallic Ca/ CaO mixture was the most effective for hydrodechlorination of about 98% of polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and polychlorinated biphenyls (PCBs) in contaminated fly ash, and also for cesium immobilization of about 96% in soil by ball-milling treatment (Mallampati et al, 2012a(Mallampati et al, , 2014Mitoma et al, 2011;Lee et al, 2015). For the present study, we developed a dry method for separating and immobilizing heavy metals in fly ash samples that is being applied to large volumes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations